2018
DOI: 10.3171/2018.2.peds17634
|View full text |Cite
|
Sign up to set email alerts
|

Assessing calvarial vault constriction associated with helmet therapy in deformational plagiocephaly

Abstract: OBJECTIVEDeformational plagiocephaly and/or brachycephaly (DPB) is a cranial flattening frequently treated in pediatric craniofacial centers. The standard of care for DPB involves patient positioning or helmet therapy. Orthotic therapy successfully reduces cranial asymmetry, but there is concern over whether the orthotics have the potential to restrict cranial growth. Previous research addressing helmet safety was limited by lack of volume measurements and serial data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Peterson et al compared DP infants with and without helmet therapy and reported no significant differences in final CrV. 21 ) The lack of significant differences in CrV with and without DP and with and without helmet therapy could guide decision-making regarding the suitability of helmet therapy for children with DP. Previous report shows that DP exacerbates until 3 months of age before spontaneously improving throughout the first 6 months of life.…”
Section: Discussionmentioning
confidence: 99%
“…Peterson et al compared DP infants with and without helmet therapy and reported no significant differences in final CrV. 21 ) The lack of significant differences in CrV with and without DP and with and without helmet therapy could guide decision-making regarding the suitability of helmet therapy for children with DP. Previous report shows that DP exacerbates until 3 months of age before spontaneously improving throughout the first 6 months of life.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used systems among the studies are the 3dMD System (3dMD Inc., Atlanta, GA, USA) [ 24 , 25 , 30 , 42 ], and the Canfield VECTRA-360 nine-pod system (Canfield Scientific, Parsippany, NJ, USA) [ 27 , 47 , 49 , 51 ], which are developed specifically for the creation of 3D models from images. The systems come with proprietary software that deals with the integration of the images into one single model.…”
Section: Reviewmentioning
confidence: 99%
“…The systems come with proprietary software that deals with the integration of the images into one single model. For the refinement of the model third-party software is used, such as Blender [ 30 , 42 ] and MeshLab [ 27 , 47 ]. The alternative to using such technology is the use of standard cameras and third-party software both for the creation of the model and for its refinement, which was described in one paper [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Petersen et al [ 8 ] investigated the extent to which helmet therapy, used in the correction of deformational plagiocephaly, resulted in constriction of calvarial growth. Their method involved retrospective review of 3dMD photographs of helmet and positioning therapy patients that were landmarked according to traditional methods, and then the landmarks were used to estimate cranial volume.…”
Section: U Ses Of 3d P Hotography In ...mentioning
confidence: 99%